Multiple Past Concussions in High School Hockey Players: Examining Cognitive Functioning and Symptom Reporting. Issue 6 (November 2021) - Iverson, Grant L.; Cook, Nathan E.; Gilman, Isabelle G.; Maxwell, Bruce; Mannix, Rebekah; Zafonte, Ross; Berkner, Paul D.; Brooks, Brian L.
Abstract : Objective: To investigate (1) if there are meaningful differences in baseline preseason cognitive functioning or symptom reporting between high school ice hockey players with and without prior concussions and (2) determine which health history variables predict symptom reporting. Design: Cross-sectional study. Setting: High schools across the state of Maine. Participants: Participants were 1616 male high school ice hockey players (mean age = 15.6 years; SD = 1.5 years) who completed baseline testing between 2009 and 2015. Independent Variables: Athletes were grouped according to their self-reported concussion history [0 (n = 1136), 1 (n = 321), 2 (n = 112), or 3+ (n = 47) previous concussions]. Main Outcome Measures: Cognitive functioning was measured by the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) battery, and symptom ratings were obtained from the Post-Concussion Symptom Scale. Results: There were no statistically significant differences between groups in cognitive functioning as measured by ImPACT. The group with ≥3 prior concussions endorsed higher total symptom scores, but the effect sizes were small and not statistically significant. In a multivariate model, prior treatment for headaches (not necessarily migraines), prior treatment for a psychiatric condition, and prior treatment for substance/alcohol use all significantly predicted total symptom scores, with concussion history being the weakest independent predictor. Conclusions: Players with a history of prior concussions performed similarly to players with no prior concussions on cognitive testing. Health history factors were more strongly associated with symptom reporting than concussion history.